Vegetales Subterráneos: Practicas Seguras para Consumidores - Amy Simonne (EDIS)
FCS8746-Span, a 2-page fact sheet by Amy Simonne, is the Spanish version of Underground Vegetables: Safe Handling Practices for Consumers (FCS8746). It gives guidelines and details on how to safely shop for and prepare vegetables grown under the ground. Published by the UF Department of Family, Youth, and Community Sciences, June 2007.